Adhesion-based sorting of blood cells: an adhesive dynamics simulation study - Dasanna, Anil Kumar; Schwarz, Ulrich S. (Soft matter, 2018)
Blood cells can be sorted in microfluidic devices not only based on their sizes and deformability, but also based on their adhesive properties. In particular, white blood cells have been shown to be sorted out by using adhesive micropatterns made from stripes that are tilted in regard to the direction of shear flow. Here we use adhesive dynamics simulations for round cells to quantitatively investigate this effect and to predict the optimal tilt angle. We then apply our method to predict optimal sorting conditions for malaria-infected red blood cells, which like white blood cells also adhere to and roll on adhesive substrates.
Gesehen am 09.01.2019